2021
DOI: 10.1161/jaha.121.021456
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Socioeconomic Disparities in Major Lower Extremity Amputation Rates in Metropolitan Areas

Abstract: Background Rates of major lower extremity amputation in patients with peripheral artery disease are higher in rural communities with markers of low socioeconomic status, but most Americans live in metropolitan areas. Whether amputation rates vary within US metropolitan areas is unclear, as are characteristics of high amputation rate urban communities. Methods and Results We estimated rates of major lower extremity amputation per 100 000 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…As a result, it is more difficult for these individuals to practice healthy behaviors, such as adequate physical activity and proper nutrition, that can help prevent PAD. Living in these distressed neighborhoods also decreases their access to primary care, specialty care, and pharmacy services, which are necessary to manage chronic conditions that are comorbidities of PAD ( 16 ). Structural racism is particularly relevant in our study, which is based on data from South Carolina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is more difficult for these individuals to practice healthy behaviors, such as adequate physical activity and proper nutrition, that can help prevent PAD. Living in these distressed neighborhoods also decreases their access to primary care, specialty care, and pharmacy services, which are necessary to manage chronic conditions that are comorbidities of PAD ( 16 ). Structural racism is particularly relevant in our study, which is based on data from South Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…However, amputation is generally considered a failure of treatment and should only be attempted after considering all other treatment options. The majority of amputations are preventable, especially among individuals with PAD who have claudication, with timely diagnosis and optimal medical treatment ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, composite prosthetic feet are expensive devices. Considering that higher lower limb amputations are more frequent in lower-income areas, lowering the costs of these devices is of extreme importance [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Chen and colleagues reported that, compared with non-Hispanic White Americans, Black patients with PAD had nearly 50% higher odds of PAD with chronic limb ischemia (CLI), and over 70% higher odds of major limb amputation [ 16 ]. Fanaroff et al similarly reported that markers of lower socioeconomic status and Black race were associated with higher rates of major lower extremity amputation [ 17 ]. Black patients with PAD may also be at an even greater risk of adverse CV events due to atherosclerotic occlusion [ 18 ].…”
Section: Introductionmentioning
confidence: 99%